Development and preliminary verification of a Monte Carlo photon transport code IMPC-Photon. (1st September 2021) - Gao, Qingyu; Fang, Peng; Zhao, Zelong; Yang, Yongwei; Wu, Xiang
Highlights: A new photon transport code IMPC-Photon has been developed. Four dominate photon-atomic reactions and secondary processes are considered to perform accurate simulation. Unified energy grid method is used to improve the speed of calculation and search of the cross section. Two photon benchmarks are employed to verify the reliability of code. Abstract: The Monte Carlo photon transport code IMPC-Photon is developed for serving the software development of designing advanced nuclear energy system such as Accelerator Driven Advanced Nuclear Energy System (ADANES) in Chinese Academy of Sciences. For photon physics, four main photon-atomic interactions and three secondary processes including atomic relaxation, electron-positron annihilation, and thick-target bremsstrahlung are implemented. For code calculations, the unified energy grid method is applied to improve the speed of searching for the cross section. Under the same computational conditions, the unified energy grid method is more time-efficient and the search efficiency is significantly improved. In addition, the "point gamma-ray source in infinite medium" and "gamma-ray skyshine experiment" benchmarks are employed to verify the reliability of the code. The results show that IMPC-Photon has a good agreement with reference codes and experimental measurement, which indicate that IMPC-Photon is reliable and credible for photon transport problem.